Evaluation of sweet sorghum (Sorghum bicolor L. Moench) used for bio-ethanol production in the context of optimizing whole plant utilization - Blümmel, Michael; Rao, S.S.; Palaniswami, S.; Shah, L.; Reddy, B.V.S. (2009)
Eighteen hybrids and 16 varieties of sweet sorghum were investigated for yields of grain, stover, juice extract for bio-ethanol distillation and bagasse and the relationships between these productive traits. There was a large degree of independency between grain and stover yields, suggesting that sweets sorghum can provide both grain and fodder yield. Juice extract yields from the stems were not significantly related to grain yields. The differences in stover fodder quality traits were significant: nitrogen content ranged from 0.44 to 0.72% in hybrids and from 0.50 to 0.89% in varieties while in vitro digestibility ranged from 43.8 to 54.5% in hybrids and from 48.8 to 54.8% in varieties. Differences in in vitro digestibility of bagasse plus stripped leaves were also substantial, ranging from 39.3 to 49.1% in hybrids and from 42.0 to 50.4% in varieties. The palatability of bagasse and stripped leaves to cattle was investigated by incorporation of the distillery residues of one sweet sorghum variety into a commercial feed block, replacing the traditionally used (non sweet) sorghum stover. There was no statistical difference in intake (DMI) and live weight gain (LWG) between bulls fed the bagasse plus stripped leaf based blocks (DMI of 3.7% of live weight and 0.73 kg/d of LWG) and bulls fed the original sorghum stover based commercial feed block (DMI of 3.5% of live weight and 0.82 kg/d of LWG). We conclude that sweet sorghum can provide food (grain), fodder (bagasse/leaf residues) and bio-ethanol at the same time.